COVID-19 and kidney diseases: A meta-analysis of clinical outcomes - Amiri, Fateme Shamekhi (Ukrainian Journal of Nephrology and Dialysis, 2021)
Abstract. Novel coronavirus 2019 (COVID-19) is a highly infectious disease that causes multiorgan failure and a high mortality rate. The present study aimed to investigate the association between COVID-19 infection and kidney dysfunction. Methods. In this meta-analysis study, 68 patients with kidney dysfunction and COVID-19 infection were analysed. Clinical features, laboratory data at initial presentation, management and, outcomes were collected. Risk of acute kidney injury (AKI), acute kidney disease (AKD) and chronic kidney disease (CKD) progression to kidney replacement therapy and graft loss were primary outcomes in this study. Results. The average age of patients at the time of diagnosis in COVID-19 nephropathy was 52.04 ± 14.42 years. There were ICU admission in 10/68 (14.7%) patients with COVID-19 nephropathy. There were a need for mechanical ventilation in 13/68 (19.1%) patients; 15/68 (22%) patients died during hospital course or post-discharge. There were AKI in 4/68 (5.8%) patients with COVID-19 nephropathy and AKD found in 14/68 (20.5%) patients with COVID-19 nephropathy during the follow-up. The median and interquartile range of SCr during the follow-up period was assessed at 1.74 mg/dl and 1.18 (Q3-Q1=2.73-1.55), respectively. The effect size of COVID-19 on AKI and AKD was assessed 0 and 0.003 using Cohen᾽s-d test. Eventually, 10 of 68 (14.7%) patients with COVID-19 nephropathy stayed on hemodialysis during the follow-up period and one of them remained on RRT but its type was not characterized. There were a total of 36/68 (52.9%) kidney transplant recipients and 10/36 (27.7%) of them developed AKI due to acute rejection. The effect size of elevated IL-6 on decreased estimated glomerular filtration rate (eGFR) in COVID-19 nephropathy was assessed 0.656 (medium effect size). Conclusion. The COVID-19 had a trivial (small) effect on eGFR declining. Future clinical research is required for investigating novel unknown findings in COVID-19 nephropathy.